KESIAPAN PETANI PADI DALAM MENGHADAPI BENCANA KEKERINGAN DI KECAMATAN BLANG BINTANG KABUPATEN ACEH BESAR - Ahmad Zaini; Yusya Abubakar; Muhammad Dirhamsyah (Jurnal Agrisep, 2016)
This research used descriptive method with farmers as respondents in Blang Bintang District, Aceh Besar. Results showed that farmers knowledge toward drought can be categorized as very high with 85-99% index value, but in some variables still need to be improved. Mitigation efforts analysis were also categorized as very high with 81-98% index value, known from data percentage of correct answers was on mitigation efforts to build/treated for facilities and infrastructures, especially to build water pump, in order to maintain water supply in rice fields that still 51,02% low. The preparation of an adequate water supply facilities and infrastructures in rice fields (to build ponds/small reservoirs) to face the drought was categorized as very low 35,71%.